Therapeutic effect of Aloe vera and silver nanoparticles on acid-induced oral ulcer in gamma-irradiated mice - Ahmed Ibrahim EL-BATAL; Salwa Farid AHMED (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Radiation combined injury, a life-threatening condition, has higher mortality than simple radiation injury. The aim of the present study was to analyze the efficiency of Aloe vera and silver nanoparticles in improving the healing of ulcerated oral mucosa after irradiation. Thirty male Albino mice were divided into five groups: control, radiation, Aloe vera (AV), silver nanoparticles (NS), and AV+NS. The mice were exposed to whole body 6Gy gamma-radiation. After one hour, 20% acetic acid was injected into the submucosal layer of the lower lip for ulcer induction. The animals received topical treatment with the assigned substances for 5 days. Lip specimens were subjected to hematoxylin and eosin and anti alpha-smooth muscle actin immunohistochemical staining. Results demonstrated occurance of ulcer three days post irradiation in all groups except in the AV+NS group where only epithelial detachment was developed. After seven days, data revealed persistent ulcer in radiation group, and almost normal epithelium in the AV+NS group. A significant reduction of epithelial thickness was detected in all groups at the third day as compared to control. At the seventh day, only the AV+NS group restored the epithelial thickness. Area percent of alpha-smooth muscle actin expression was significantly decreased in radiation group at the third day followed by significant increase at the seventh day. However, all treatment groups showed significant increase in alpha-smooth muscle actin at the third day, which decreased to normal level at the seventh day. Our study demonstrated the efficiency of Aloe vera and silver nanoparticles in enhancing ulcer healing after irradiation.